Status Jumlah Leukosit pada Petani Garam di Desa Romokalisari Kecamatan Benowo Kota Surabaya: Status of Leukocyte Count in Salt Farmers in Romokalisari Village, Benowo District, Surabaya City - Fitrotin Azizah; Nur Vita Purwaningsih; Yeti Eka Puspita Sari; Salwa Sausan Salsabila (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
White blood cells or leukocytes are an important component that acts as an immune system in the blood. Salt farmers work under hot sun exposure and lack the understanding to wear personal protective equipment, which causes the body's resistance to decrease so that the number of leukocyte cells also decreases. The number of leukocytes is reduced, making the body susceptible to infection. Immunity is resistance to several diseases, namely against infectious diseases. This study aims to describe the results of examining leukocyte cell counts in salt farmers in Romokalisari Village. This study uses a descriptive method conducted by observation. The sample in the study was all salt farmers, as many as 25 people. The results showed that the salt farmers examined did not experience abnormalities in the number of leukocytes. However, there was an increase in the number of eosinophils from the normal value of 6 out of 25 samples with a percentage of 24%. The conclusion from the samples examined obtained the results of 84% normal leukocytes, and 16% got abnormal leukocyte results, so salt farmers can be said to be healthy.